Intergenerational mobility in education and occupation and the effect of schooling on youth's earnings in Brazil - Marcos O. Garcias; Ana Lúcia Kassouf (EconomiA, 2021)
This study uses data from the International Labor Organization's 2013 school-to-work transition survey (SWTS) to measure intergenerational educational and occupational mobility in Brazil. The SWTS database contains information on youths from 15 to 29 years old as well as on family's socioeconomic characteristics, both current and retrospective. This data set permits the measurement of intergenerational mobility. The results obtained show great intergenerational educational mobility, especially when parents had lower levels of education, and slightly less occupational mobility. To analyze the returns to education, earnings equations were estimated using the Heckman selection model. The education of youths and their parents had a great impact on youths' earnings, mainly on females. Young women with higher education more than double their earnings compared to those without high school.
Keywords: 330; Intergenerational mobility; Male and female youths; Occupation; Education; Earnings